A 65‐Year‐Old Woman Diagnosed With PHACE Syndrome. Issue 6 (28th December 2012) - Burch, Ezra A.; Garzon, Maria C.; Parikh, Anuraag; Meyers, Philip M.
Abstract PHACE syndrome is characterized by the association between infantile hemangioma and varied but characteristic systemic manifestations, including cerebrovascular and cardiac abnormalities. The disorder has primarily been diagnosed in children, with little information available regarding long‐term outcomes in affected individuals. We report the oldest known individual with PHACE syndrome in the medical literature, a 65‐year‐old woman who was diagnosed after a transient ischemic attack.